ARTIFICIAL INTELLIGENCE AND AUDIO MEDIA: A DEVELOPMENT MODEL OF RADIO JOURNALISM IN THE NEW ERA (International Conference on Modern Science and Scientific Studies, 2025)
This article analyzes the impact of artificial intelligence (AI) technologies on radio journalism and the field of audio media, as well as the development model of this industry in the new era from a futurological perspective. The study examines innovative processes such as AI-based automatic voice synthesis, content generation, audience analysis, and interactive podcasts. The integration of artificial intelligence into journalistic processes is evaluated as an essential factor in the digital transformation of Uzbekistan’s radio broadcasting. The article highlights the prospects of radio journalism up to 2030, its ethical challenges, and the issues of human–technology collaboration within a futurological framework.